Classifications of People Addicted to Work, Treatment and Measurement of Workaholism – A Case Study - Dobrowolska, Małgorzata; Izydorcyzk, Bernadetta (European Journal of Economics and Business Studies, 2017)
The paper presents the typologies of persons addicted to work, with the description of three case studies. At the end, information has been provided concerning treatment and measurement of workaholism. The classifications described in the paper are presented after Szpitalak, (2012, pp. 61-67). In accordance with the definitions concerning the functioning of workaholics, provided in literature sources, it is worth pointing out that such a person experiences specific emotions, thoughts and behaviour, typical for addiction. A common feature of psychological pattern of workaholic functioning is the compulsion, experienced and expressed in actions, as well as the excessive, and not controlled by the person’s will, involvement of a person in work, beyond reasonable time limits, and the compulsion to subjugate and execute all actions in the person’s life to professional activity only. A workaholic may reveal various profiles of psychological traits that determine her/his actions in a work situation and continuous thinking about work. Work situation becomes paramount in determining and motivating the direction of all life’s actions. In literature, it is possible to delineate several typologies of psychological traits for people labelled as workaholics.
Keywords: workaholism, addiction to work, treatment, measurement, case study